Peri-intraventricular hemorrhage and oxidative and inflammatory stress markers in very-low birth weight newborns - Jamil P.S. Caldas; Carolina A. Braghini; Taís N. Mazzola; Maria M.S. Vilela; Sérgio T.M. Marba (Elsevier, 2015)
Objectives: To evaluate the association between oxidative and inflammatory stress markers with peri-intraventricular hemorrhage (PIVH) in very-low birth weight newborns. Methods: This was a prospective study conducted in a level III neonatal unit. Basal and stimulated reactive oxygen intermediates (ROIs), reduced glutathione (GSH), and interleukin-6 (IL-6) levels were measured in umbilical cord blood. Newborns underwent serial ultrasound at the bedside, at 6, 12, 24, and 72 hours of life and at seven days for the diagnosis of PIVH, classified as grades I to IV. Two groups were assessed, those with and without PIVH; maternal and neonatal control variables were used for comparison. Univariate and multiple regression analyses were applied. Results: A total of 125 newborns were assessed. PIVH incidence rate was 12.0%. In the univariate analysis, basal ROI, the use of two or more doses of corticosteroids, birth weight < 1,000 g, ventilatory support use, and SNAPPE II value ≥ 22 were significantly associated with PIVH. However, in the multivariate analysis, only antenatal steroid use was independently associated with the disease (OR 0,194; 95% CI: 0,048 to 0,773; p=0,02). Conclusion: ROI, GSH, and IL-6 levels were not associated with the occurrence of PIVH in very-low birth weight infants Resumo: Objetivos: avaliar a associação entre marcadores de estresse oxidativo e inflamatório com a hemorragia peri- e intraventricular (HPIV) em recém-nascidos (RN) de muito baixo peso ao nascer. Métodos: estudo prospectivo em unidade neonatal nível III. Foi feita dosagem em sangue de cordão umbilical de intermediários reativos de oxigênio (ROI) basal e estimulado, glutationa reduzida (GR) e interleucina-6 (IL-6). Recém-nascidos foram submetidos à ultrassonografia seriada, à beira do leito, com 6, 12, 24 e 72 horas de vida e 7 dias para o diagnóstico de HPIV, classificada em graus de I a IV. Foram avaliados dois grupos: com e sem HPIV e variáveis de controle maternas e neonatais foram usadas para comparação. Análise univariada e de regressão múltipla foram aplicados. Resultados: foram avaliados 125 recém-nascidos. A taxa de incidência de HPIV foi de 12,0%. Na análise univariada o valor basal de ROI, o uso de duas ou mais doses de corticosteroide, peso ao nascer menor que 1.000 g, o uso de assistência respiratória e valor de SNAPPE II maior ou igual a 22 foram significativamente associados à HPIV. Porém, na análise multivariada, apenas o uso antenatal de esteroides se mostrou independentemente associado à doença (OR 0,194 IC95% 0,048-0,773 p=0,02). Conclusão: ROI, GR e Il-6 não foram associados à ocorrência de HPIV em RN de muito baixo peso ao nascer Keywords: Oxidative stress, Reactive oxygen species, Interleukin-6, Glutathione, Intraventricular hemorrhage, Newborn, Palavras-chave: Estresse oxidativo, Espécies de oxigênio reativas, Interleucina-6, Glutationa, Hemorragia cerebral, Recém-nascido